PI3K in human oesophageal squamous carcinoma cells : a critical modulator in the PKB signalling pathway - Shaw, Nicolene (My University, 2013)
The phosphotidylinositide-3-kinase (PI3K) pro-survival signalling pathway is critical in the development of cancer. Major contributors to the proliferative and/or anti-proliferative signalling in human oesophageal squamous cell carcinoma (HOSCC) are currently unknown. Based on the Ser473 phosphorylation state of PKB (pPKB), this study dissects the overall activation status of the PI3K/PKB pathway. Despite the prevalent membrane expression of PI3K determined through western blotting and immunofluorescence, pPKB levels were shown to be surprisingly low. Activation of EGFR did not produce a hyperactivation of the PI3K/PKB pathway. Neither PI3K nor PKB sequence isolated from the 5 HOSCC cell lines possessed any of the ―hotspot‖ mutations described previously for other tumours. Inhibiting phosphatase protein 2A (PP2A), an integral antagonist of PKB, indicated that its activity in respect of PKB is diminished in HOSCC cells. Despite the low concentration of pPKB, the reciprocal relationship with PTEN expression was not evident in the WHCO and SNO HOSCC series. Moreover, reversible oxidization and inhibition of PTEN served to augment the activation of the PI3K/PKB pathway. Since oxidation of PTEN is imperative for effective signal propagation from activated EGFR and PI3K, these data reveal an aberrant EGFR-PI3K-H2O2 mediated PTEN inhibition in HOSCC. Allied to this discovery, was the finding that HOSCC cells are highly susceptible to oxidative stress induced by H2O2. This was suggested to play an essential part in maintaining the low PI3K/PKB activation status. Although the decrease in PTEN activity was required for the induction of pPKB, PTEN may not be the only limiting component for the activation of the PI3K/PKB pathway in HOSCC. In addition to its overexpressed EGFR status, the WHCO and SNO HOSCC series have the propensity to appropriate nuclear β-catenin. Interruption of the PI3K/PKB signalling pathway caused a small, yet significant, depression in the nuclear localization of β-catenin in 3 of the HOSCC cell lines. Together, this work greatly expands our understanding of the major influences behind the proliferative and/or anti-proliferative signalling in HOSCC, primarily that, the EGFR overexpression status does not propagate these transforming capabilities via activation of the PI3K/PKB pathway, and that this may be a reflection of its transformation potential. The findings derived from this study are likely to have a profound impact on future therapeutic targets for this disease.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2011.
Keywords: Esophagus - cancer.; Cell differentiation.; Biological response modifiers.; Cancer